An Application of Operative Trans-resistance Amplifier and its Simulation - prasad Tripathy, Hara; Pattanai, Priyabrata (International Journal of Psychosocial Rehabilitation, 2025)
This work offers grounding inductor simulation by employing “Operational Transresistance Amplifiers that could be replaced by actual inductor. The variation in the induction values can be varied with in variation of the resistance and capacitance of the passive elements. The passive elements are grounded. The simulation of the inductor is discussed for displaying the compatibility with more complexed circuits. The workability of circuit had been performed into the PSPICE. Every simulating result had been provided